ОТНОШЕНИЕТО КЪМ ВРЕМЕТО КАТО КУЛТУРНА НОРМА. - СОТИРОВА, ДАНИЕЛА (Philosophical Alternatives Journal / Filosofski Alternativi, 2024)
The attitude toward time is seen as a cultural norm that is essential for the harmonization of intercultural communications. A philosophical-anthropological study of the perception of time is provided here. Different types of time are considered. The constructs of time perspective and cultural intelligence are introduced. It is being discussed whether "slow" is a Bulgarian cultural norm, i.e., whether "Despacito" is the national anthem of Bulgaria, according to the Siri app - the errors propagated by the computer programs going around the world should be refuted. As a way to achieve this, in the article, a systematic philosophical and analytical review of the concepts of relation to time is presented. Specifics related to the concepts of mental models, cultural intelligence, and cultural clusters are proposed. They can be helpful in understanding cultural differences and communicating more effectively.